The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fnins.2019.00149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leg Motor Imagery Combined With Electrical Stimulation on Plasticity of Corticospinal Excitability and Spinal Reciprocal Inhibition

Abstract: Motor imagery (MI) combined with electrical stimulation (ES) enhances upper-limb corticospinal excitability. However, its after-effects on both lower limb corticospinal excitability and spinal reciprocal inhibition remain unknown. We aimed to investigate the effects of MI combined with peripheral nerve ES (MI + ES) on the plasticity of lower limb corticospinal excitability and spinal reciprocal inhibition. Seventeen healthy individuals performed the following three tasks on different days, in a random order: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
4
24
0
Order By: Relevance
“…When motor imagery was provided by means of watching and imagining actions shown on a pre-recorded video of grasping, while not producing the movements, it was shown that concurrent electrical stimulation facilitated MEP corticospinal excitability and that either motor imagery and electrical stimulation alone did not elicit any effects [ 157 ]. Similar acute effects were shown using combined motor imagery and electrical stimulation of the lower-limbs [ 137 ]. Preliminary results with chronic stroke patients also suggest that applying electrical stimulation in combination with motor imagery over the course of 10 days may possibly improve upper-limb function after the intervention cessation [ 106 ].…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervesupporting
confidence: 66%
“…When motor imagery was provided by means of watching and imagining actions shown on a pre-recorded video of grasping, while not producing the movements, it was shown that concurrent electrical stimulation facilitated MEP corticospinal excitability and that either motor imagery and electrical stimulation alone did not elicit any effects [ 157 ]. Similar acute effects were shown using combined motor imagery and electrical stimulation of the lower-limbs [ 137 ]. Preliminary results with chronic stroke patients also suggest that applying electrical stimulation in combination with motor imagery over the course of 10 days may possibly improve upper-limb function after the intervention cessation [ 106 ].…”
Section: Brain-controlled Electrical Stimulation Of Muscles and Nervesupporting
confidence: 66%
“…Cortical excitability modulation over corticospinal or corticomuscular connectivity (i.e., over the sensorimotor loop) has been demonstrated using transcranial magnetic stimulation (Fujisawa et al, 2011). Recent experiments investigated the relevant role of peripheral sensory stimulation intensity in influencing corticomotor excitability (Takahashi et al, 2019). While intensities above-motor-threshold induced stronger corticomotor output measured by means of motor evoked potentials (MEP), the results for stimulation below motor threshold led to no agreement, probably due to the wide range of stimulation parameters used in the existing literature (Carson and Buick, 2019;Chipchase et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The power change was computed as the percentage of increase or decrease in power (i.e., ERS or ERD) with respect to the baseline ([-2.5, -1.5] s), as described in Equation 4.From the time-frequency maps, we calculated the mean change in power of channels C1, C3, CP1 and CP3 (i.e., area over the sensorimotor cortex representing right forearm, contralateral hemisphere to the stimulated limb), since we considered that averaged values over these electrodes could better quantify the overall changes in the sensorimotor areas. We calculated the sensorimotor averaged changes in power in alpha[7][8][9][10][11][12][13] Hz and beta[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz bands for non-stimulation ([-3, -1] s) and NMES ([0.5, 2.5] s) intervals, using as baseline the [-2.5, -1.5] s interval (seeFigure 3). The NMES period was defined as starting at 0.5 s to avoid potential bias and influence of the stimulation onset like event-related brain potentials (e.g., error potentials, P300, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One potential mechanism is the increase of corticospinal gain modulation ( Khademi et al, 2018 , 2019 ; Naros et al, 2019 ). The focus of previous studies has been on the induced changes at the cortical level ( Gharabaghi, 2016 ), although there is some research on spinal changes following intervention at the lower limb ( Takahashi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%